The Impact of HR Analytics Usage Frequency on Retention Effectiveness and Attrition Control: A Logistic Regression Approach - Vidya Nayak, Shankar Chaudhary, Chitralekha Kumar (Journal of Informatics Education and Research, 2025)
It is well known that the two most significant factors that affect an organization's performance are attrition and retention. In recent times, organizations are experiencing increase in retention and decrease in attrition due to implementation of HR Analytics. The purpose of this research paper is to study the relationship between the frequency of HR analytics usage and its impact on retention and attrition management. We have used Logistic Regression method to study the relationship between influence of HR analytics with retention and attrition. The logistic regression analysis assessed the relationship between HR analytics usage for attrition and retention with retention effectiveness and likewise for attrition control.